Effects of 2-Year-Long Maintenance Training and Detraining on 558 Subacute Ischemic Stroke Patients' Clinical-Motor Symptoms - Tollár, József; Vetrovsky, Tomas; SZéPHELYI, Klaudia; Csutorás, Bence; Prontvai, Nándor; Ács, Pongrác; Hortobágyi, Tibor (Medicine and science in sports and exercise, 2023)
PURPOSE: This study aimed to determine the effects of a 2-yr-long maintenance training (MT) exergaming and detraining (DT) on clinical-motor symptoms in subacute ischemic patients with stroke (PwST). The hypothesis was that MT motor rehabilitation program would further increase the effects of the initial rehabilitation. METHODS: After high-intensity and high-frequency exergaming twice or once a day, 5 times per week for 5 wk (EX2: 50 sessions; EX1: 25 sessions, results reported previously), 558 PwST were randomized to EX2-MT, EX2-DT, EX1-MT, and EX1-DT. MT exergaming consisted of once a day, 3 times per week for 2 yr, and DT did not train. Outcomes were measured at 6, 12, 18, and 24 months. The data were analyzed using longitudinal linear mixed-effects models and general linear hypotheses testing. RESULTS: Modified Rankin Score (primary outcome), body mass, Mini-Mental State Examination score, Beck Depression Inventory, measures of quality of life, Berg Balance Scale, 6-min walk test, and four measures of center of pressure path tended to retain the initial rehabilitation-induced gains in the MT patients in selected outcomes (especially walking capacity). The scores tended to mildly worsen after DT, partially supporting the hypothesis. CONCLUSIONS: MT successfully maintained, but only in selected variables did it further increase the initial exergaming rehabilitation-induced robust improvements. DT modestly reduced the initial exergaming rehabilitation-induced improvements. MT programs might be needed after initial stroke rehabilitation to reduce subsequent losses of quality of life and further improve clinical-motor symptoms.
Keywords: výsledek terapie; Exercise Therapy; cévní mozková příhoda; ischemická cévní mozková příhoda; rehabilitace po cévní mozkové příhodě; Ischemic Stroke; Humans; Stroke; Stroke Rehabilitation; Quality of Life; terapie cvičením; Treatment Outcome; kvalita života; lidé